China’s Agriculture "Going Out" Strategy beyond Resource Constraints and Unbalanced Trading - Morshed, Monzur (American Journal of Trade and Policy, 2018)
Implementation of agricultural "going out" strategy is the effective way to co-ordinate the use of international and domestic markets and resources, and to expand the breadth and depth of Agriculture in China. With the continual increase of industrialization and urbanization, agricultural production in China is conditioned by the limitation of cultivated land resources and fresh water resources, also impacted by exhaustion of soil, by frequent drought and floods. At the same time, China’s agriculture trade also faces unbalanced situation and unfair international environment. Therefore, accelerating the implementation of the agriculture "going out" strategy, not only can effectively break through the bottleneck of agricultural development in the constraint of resources, get out of market monopoly from international agricultural multi-national companies, but also can give full play to advantages of our foreign exchange reserves to ensure the (supply effectiveness) of agricultural products in China. However, at present China’s agriculture "going out" strategy hasn’t got significant achievements, there are some problems such as slow growth in foreign investment in agriculture, regional centralization of investment, the small quantities and small scale of investment companies, and the lack of international agricultural professionals. For these reasons, the relevant government departments should increase financial support to encourage agricultural enterprises "going out"; speed up the training of professionals to create giant agricultural transnational corporations, resulting in occupying reasonable seats in global agricultural supply chain, and establishing China as resourceful agricultural trading nations.